(untitled) (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2026)
The decline in corn production due to leaf blight reached 15%, equivalent to US1.0 billion. In South Sumatra, the incidence of leaf blight disease in corn plants reached 98%. However, there have been few reports on the various pathogens that can cause corn leaf blight in South Sumatra. The purpose of this study was to determine the incidence of disease, the intensity of disease attack, and the diversity of fungal pathogens causing leaf blight disease in Tanjung Pering Village, North Indralaya, South Sumatra. The methods used in this study were observation of disease incidence and disease attack intensity, and purposive random diagonal sampling of plants. Observations were conducted at weekly intervals for five times, and the plant samples were identified at the Plant Pathology Laboratory of the Department of Plant Pests and Diseases. The results show that the incidence of corn leaf blight reached 100% with an average disease intensity of 28.60%. Identification of the pathogens causing the disease revealed differences in fungal species and numbers between observations. The diversity index for each observation was <1, and the dominance index was small or close to 0. The pathogenic fungi causing corn leaf blight consisted of B. sacchari, B. maydis, B. panici-miliacei, B. oryzae, H. juglandinum, H. microsorum, H. quercicola, H. velutinum, C. pseudobrachyspora, and C. dactyloctenicola. Thus, based on the observation results, the intensity of leaf blight disease attack was classified as low, with a low species diversity index and a low dominance index.